ALAT PENYARINGAN AIR KOTOR MENJADI AIR BERSIH MENGGUNAKAN MIKROKONTROLLER ATMEGA 32 - Diko Susanto; Toibah Umi Kalsum; Yanolanda Suzantri H (Jurnal Media Infotama, 2014)
Formulation of the problem is to make dirty water filtration equipment into clean water using a microcontroller AT-mega32. Software used includes operating systems, programming languages and software pengelolah data. The operating system used by Microsoft Windows 7 as the operating system. The programming language used is the programming language Basic - BASCOM AVR and Visual Basic 6.0. The test is done by testing the screening tool dirty water into clean water in line with expectations and design. Ie the sensor can detect the level of water clarity and filtered water sources and displayed on the LCD 16 x 2 and PC applications with sizes percent.Keywords: Sensors, Water and Microcontroller